Responding to the character education on the tradition of mopolihi lo limu (lemon bathing) at Gorontalo - Razak H. Umar (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
Character building has become strategic way for government to prepare Indonesian golden generation on 2045. President Regulation Number 87 Year 2017 about Reinforcement of Character Education (PPK) suggests 18 students’ character value through the harmony of psyche building, sense building, thought building, and physical building. Those could be implemented through the development of local wisdom and the improvement of special character and identity of a region. Gorontalo is one of nineteen regions in Indonesia which regulates local laws has various local laws, one of them is Mopolihu Lo Limu (Lemon Bathing) for female children under 1 to 3 years old. Mopolihu Lo Limu tradition has numbers of values which are relevant to the Reinforcement of Character Education (PPK) such as: (1) Religiosity, (2) Honesty, (3) Tolerance, (4) Discipline, (5) Hard work, (6) Independent, (7) Love the Mother Land, (8) Friendly, (9) Love Peace, (10) Social Awareness, (11) Environment Awareness and (12) Responsible. This research used descriptive qualitative method which was relevant to the object. It took place at Gorontalo as the research setting. The object of the research was the Mopolihu Lo Limu  (Lemon Bathing) for female children.